Everyday life and everyday learning: the ways in which pre-service teacher education curriculum can encourage personal dimensions of teacher identity - Amélia Lopes (2012)
This article presents and discusses the findings of a research project, the main objective of which is to identify curriculum components that promote personal development as a nuclear part of teacher professional identity formation through pre-service teacher education. Curriculum is viewed as an ecological scenario with different subsystems and both as formal and informal. Identity formation is conceived as an ever-provisional result of a double transaction: the biographical one and the relational one. The curricula of four different historical periods of pre-service teacher education in Portugal and the professional identity of teachers trained within them were characterised through collection and analysis of documents and biographical narratives. Crossing results from the four periods, the quality of school climate emerges as an important variable to the quality of the teachers' identity. The lifelong learning ethos seems to emerge when the training curriculum connects everyday learning with everyday life, namely by urging the students' involvement in school life, peer learning activities and peer and teacher educators' informal learning activities.